Towards the elimination and eradication of hepatitis B - Geoffrey Dusheiko (Elsevier, 2015)
Despite the introduction of vaccination, chronic hepatitis B remains a major cause of liver-related morbidity and mortality including cirrhosis, decompensated cirrhosis and hepatocellular carcinoma. Maintenance antiviral therapy is required for most people, as low rates of cure occur. The stated aim of therapy presently is HBV DNA suppression; effective suppression of viral replication is associated with significant reductions in morbidity from end-stage liver failure and to an extent, hepatocellular carcinoma. Unfortunately, major barriers to cure, such as a reservoir of episomal covalently closed circular DNA (cccDNA) (the HBV minichromosome), and a dysfunctional immune response, pose challenges. These barriers will need to be overcome to ensure higher rates of cure than can be achieved presently.Quantitative and diagnostic testing for HBV DNA is not generally available, hampering effective monitoring and treatment in low-income countries. The majority of patients in resource-constrained countries are not identified before the onset of cirrhosis. Without coordinated action, and transfer of new diagnostic technologies and treatments to low-income countries, recent therapeutic advances will have little effect on the global burden of disease.A shift to curative treatment for the majority would be a major advance in the elimination of hepatitis B. New and improved molecular therapeutics and immunological strategies for the treatment of chronic hepatitis are emerging, however. A number of promising lines of development are in progress. A curative regimen may require a combination of viral suppression via nucleoside analogue therapy to prevent cccDNA amplification and viral propagation, safe selective cccDNA inhibitors to deplete, silence or degrade cccDNA, agents to block the entry of HBV into the hepatocyte plus compounds to prevent capsid assembly and cccDNA interactions. Targeted immune activation could restore the exhausted immune cell repertoire.